THE EFFECTS OF AN INNOVATIVE TECHNOLOGY APPLIED AS VIRTUAL REHABILITATION ON CLINICAL OUTCOMES IN ANTERIOR CRUCIATE LIGAMENT INJURY - POLAT, MİNE GÜLDEN; AYDOĞDU, ONUR; YURDALAN, SAADET UFUK; SARI, ZÜBEYİR (CENTRAL BOHEMIA UNIV, 2017)
In recent years, many different technologies on virtual rehabilitation have been produced and used in research. However, existing studies are limited because most of them focus on the balancing ability of the elderly or studied stroke patients with same systems. Thus, it is necessary to investigate the effects of a new virtual rehabilitation system in patients with Anterior Cruciate Ligament (ACL) Reconstruction. The purpose of this study was to investigate the effects of a virtual rehabilitation system using a MarVAJED (R) system which provides visual and auditory stimulus aimed at educating and controlling the joint proprioception, range of motion, pain intensity, and knee swelling in individuals with an ACL injury. A total of fifteen patients with ACL reconstruction participated in this study. In addition to conventional physiotherapy, a virtual rehabilitation treatment was applied with visual and auditory stimulus for a total of eight weeks, three sessions per week. There were statistically significant improvements in measures of proprioception, range of motion, pain intensity, and knee swelling between pre- and post - treatment (p<0.05). We concluded that this new VR system known as MarVAJED effectively treat ACL patients by improving proprioception, range of motion, and by decreasing pain intensity, and knee swelling.
Keywords: Innovative Technology; Rehabilitation; Physiotherapy; KNEE; RECONSTRUCTION; RELIABILITY; EXERCISE; MOTION; RANGE; PAIN